2021
DOI: 10.3389/fneur.2021.623358
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Brain Metabolism in Patients at Risk of Sudden Unexpected Death in Epilepsy

Abstract: Objective: To characterize regional brain metabolic differences in patients at high risk of sudden unexpected death in epilepsy (SUDEP), using fluorine-18-fluorodeoxyglucose positron emission tomography (18FDG-PET).Methods: We studied patients with refractory focal epilepsy at high (n = 56) and low (n = 69) risk of SUDEP who underwent interictal 18FDG-PET as part of their pre-surgical evaluation. Binary SUDEP risk was ascertained by thresholding frequency of focal to bilateral tonic-clonic seizures (FBTCS). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…These studies observed MRI evidence of atrophy of the PAG and raphe nuclei among other sites in PWE who died from SUDEP. [236][237][238][239][240][241] A recent positron emission tomography scan study in PWE who exhibited a high frequency of focal to bilateral tonic-clonic seizures and are proposed to be at high risk for SUDEP observed that several structures, including the PAG, exhibited significant metabolism increases interictally, as compared to a low-risk patient 242 The authors suggest that these findings may actually be indicative of loss of neuronal function, gliosis, and/or active inflammatory responses.…”
Section: Human Neuroimaging Changes In Sudepmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies observed MRI evidence of atrophy of the PAG and raphe nuclei among other sites in PWE who died from SUDEP. [236][237][238][239][240][241] A recent positron emission tomography scan study in PWE who exhibited a high frequency of focal to bilateral tonic-clonic seizures and are proposed to be at high risk for SUDEP observed that several structures, including the PAG, exhibited significant metabolism increases interictally, as compared to a low-risk patient 242 The authors suggest that these findings may actually be indicative of loss of neuronal function, gliosis, and/or active inflammatory responses.…”
Section: Human Neuroimaging Changes In Sudepmentioning
confidence: 99%
“…251 Another recent criterion for SUDEP susceptibility was based on the relatively high frequency of focal to bilateral tonic-clonic seizure occurrence in PWE. 242 An automated approach to SUDEP prevention, involving medical intervention to be administered via an implanted device automatically delivering electrical stimulation or medication, has recently been proposed, 252 and a peripheral approach using diaphragmatic pacing in a SUDEP model has recently been published. 253 Once criteria for SUDEP susceptibility are validated, preventative approaches should be employed.…”
Section: Preventative Approachesmentioning
confidence: 99%
“…Brainstem dysfunction has been implicated in SUDEP pathophysiology and altered patterns of brain metabolism have been demonstrated in patients at high risk of SUDEP. 32 Both alterations in serotonin and adenosine neurotransmission may be involved in SUDEP pathophysiology. 8,30 Serotonergic neurons influence the hyperexcitability of the brainstem respiratory center; dysfunction in serotonin has been implicated in sudden infant death syndrome and possibly SUDEP.…”
Section: Adenosine and Serotonergic Medicationsmentioning
confidence: 99%
“…Brainstem dysfunction has been implicated in SUDEP pathophysiology and altered patterns of brain metabolism have been demonstrated in patients at high risk of SUDEP 32 . Both alterations in serotonin and adenosine neurotransmission may be involved in SUDEP pathophysiology 8,30 .…”
Section: Sudep Preventionmentioning
confidence: 99%